A regional application of the MAGIC model in Wales: calibration and assessment of future recovery using a Monte-Carlo approach - Sefton, C. E. M.; Jenkins, A. (Hydrology and earth system sciences, 1998)
A survey and resurvey of 77 headwater streams in Wales provides an opportunity for assessing changes in streamwater chemistry in the region. The Model of Acidification of Groundwater In Catchment (MAGIC) has been calibrated to the second of two surveys, taken in 1994-1995, using a Monte-Carlo methodology. The first survey, 1983-1984, provides a basis for model validation. The model simulates a significant decline of water quality across the region since industrialisation. Agreed reductions in sulphur (S) emissions in Europe in accordance with the Second S Protocol will result in a 49% reduction of S deposition across Wales from 1996 to 2010. In response to these reductions, the proportion of streams in the region with mean annual acid neutralising capacity (ANC) > 0 is predicted to increase from 81% in 1995 to 90% by 2030. The greatest recovery between 1984 and 1995 and into the future is at those streams with low ANC. In order to ensure that streams in the most heavily acidified areas of Wales recover to ANC zero by 2030, a reduction of S deposition of 80-85% will be required.